2009
DOI: 10.1542/peds.2008-1439
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Morbidity and Cost Differences Between Late-Preterm and Term Infants During the First Year of Life

Abstract: Late-preterm infants have greater morbidity and total health care costs than term infants, and these differences persist throughout the first year of life. Management strategies and guidelines to reduce morbidity and costs in late-preterm infants should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
169
2
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(195 citation statements)
references
References 17 publications
10
169
2
14
Order By: Relevance
“…These authors reported that 3.4% and 3% of a cohort of 371 late preterm infants were at increased risk of being underweight at 1 and 2 years of age, respectively. These findings could be partly explained by the negative effect on growth associated with the higher hospitalization rates reported for late preterm infants in the first years of life (12,13). In addition, as the prevalence of late preterm birth in the population studied was higher in the low-income families, the late preterm infants enrolled in that study could present environmental and economic constraints on growth.…”
Section: Discussionmentioning
confidence: 85%
“…These authors reported that 3.4% and 3% of a cohort of 371 late preterm infants were at increased risk of being underweight at 1 and 2 years of age, respectively. These findings could be partly explained by the negative effect on growth associated with the higher hospitalization rates reported for late preterm infants in the first years of life (12,13). In addition, as the prevalence of late preterm birth in the population studied was higher in the low-income families, the late preterm infants enrolled in that study could present environmental and economic constraints on growth.…”
Section: Discussionmentioning
confidence: 85%
“…1 -5 Premature infants without significant complications, who make up the majority of NICU patients, have postdischarge costs >3 times those of their term peers. 5 Additionally, discharge increases parental anxiety, which is linked to increased risks of acute care visits after NICU discharge. 6 Families of low socioeconomic status (SES) and of minority race or ethnicity may be at even higher risk.…”
Section: What This Study Addsmentioning
confidence: 99%
“…An American, retrospective and multi-center study, reported that 45% of 3,787 children in a program monitoring the pre-term infants were hospitalized in the first year of life, especially for respiratory causes (14) . Lower rates (15.2%) were described by another study, which examined re-hospitalizations and their causes in the first year of life of 1,683 NB with a gestational age of > 33 (15) . A likely explanation for a lower rate of re-hospitalization was that the authors monitored PTI between 33 and 36 weeks, unlike the present study, which monitored all PTI below 37 weeks.…”
Section: Discussionmentioning
confidence: 91%